Genome-wide identification of NAC transcription factors and regulation of monoterpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ahmed, Jawad; Sajjad, Yasar; Gatasheh, Mansour K.; Ibrahim, Khalid Elfaki; Huzafa, Muhammad; Khan, Sabaz Ali; Situ, Chen; Abbasi, Arshad Mehmood; Hassan, Amjad (Frontiers in Plant Science, 2023)
NAC transcription factors (TFs) are crucial to growth and defense responses in plants. Though NACs have been characterized for their role in several plants, comprehensive information regarding their role in Catharanthus roseus, a perennial ornamental plant, is lacking. Homology modelling was employed to identify and characterize NACs in C. roseus. In-vitro propagation of C. roseus plants was carried out using cell suspension and nodal culture and were elicited with two auxin-antagonists, 5-fluoro Indole Acetic Acid (5-F-IAA) and α-(phenyl ethyl-2-oxo)-Indole-Acetic-Acid (PEO-IAA) for the enhanced production of monoterpenoid indole alkaloids (MIAs) namely catharanthine, vindoline, and vinblastine. Analyses revealed the presence of 47 putative CrNAC genes in the C. roseus genome, primarily localized in the nucleus. Phylogenetic analysis categorized these CrNACs into eight clusters, demonstrating the highest synteny with corresponding genes in Camptotheca acuminata. Additionally, at least one defense or hormone-responsive cis-acting element was identified in the promoter region of all the putative CrNACs. Of the two elicitors, 5-F-IAA was effective at 200 µM to elicit a 3.07-fold increase in catharanthine, 2.76-fold in vindoline, and 2.4-fold in vinblastine production in nodal culture. While a relatively lower increase in MIAs was recorded in suspension culture. Validation of RNA-Seq by qRT-PCR showed upregulated expression of stress-related genes (CrNAC-07 and CrNAC-24), and downregulated expression of growth-related gene (CrNAC-25) in elicited nodal culture of C. roseus. Additionally, the expression of genes involved in the biosynthesis of MIAs was significantly upregulated upon elicitation. The current study provides the first report on the role of CrNACs in regulating the biosynthesis of MIAs.